Hubungan Sikap Ibu dengan Keaktifan dalam Kegiatan Posyandu Balita di Wilayah Kerja Puskesmas Pucang Sewu Kota Surabaya - Dyas Dwi Arianti; Novera Herdiani; Kardita Puspa Monitasari (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
The frequency of weighing children under five ≥ 8 times in 1 year in 2018 was 54.6% with a national target of 85%. This shows that the percentage is still below the national target. The purpose of this study was to analyze the attitude of mothers with activeness in toddler posyandu activities. This type of research is a quantitative analytic study with a cross sectional approach. The research was conducted in the working area of ​​the Pucang Sewu Public Health Center, Surabaya City in April 2023. The population in this study were all mothers who had children under five years of age with a sample of 50 respondents. The instrument in this study was a mother's attitude questionnaire consisting of 26 questions and 4 answer choices. Data processing techniques using statistical tests with the help of SPSS with the Chi Square test. This study shows that the p-value is 0.001 <0.05, which means that there is a relationship between the mother's attitude and activeness in the activities of the Toddler Posyandu in the Working Area of ​​the Pucang Sewu Health Center, Surabaya City. To increase the activity of mothers by providing guidance to Posyandu cadres to motivate mothers of toddlers to always be active in Posyandu visits which can be done every month and provide counseling to mothers of toddlers related to the positive impact that is obtained when routinely bringing toddlers to the Posyandu.